Improvement of Forage Nutritive Quality of Alfalfa and Red Clover through Plant Breeding - Marijana Tucak (MDPI AG, 2021)
Alfalfa and red clover are important perennial legumes for the production of high-quality fodder. The improvement of the forage quality of legumes is one of the strategic goals of breeding programs. Variation in quality traits (protein content (CP), neutral detergent fiber content (NDF), and acid detergent fiber content (ADF)) and relative feed value (RFV) among seven cultivars and 39 elite breeding populations of alfalfa and red clover was evaluated in the study. Significant differences were determined among the investigated cultivars/populations. Alfalfa populations L-8, 10, 12, 15, and 20 were characterized by a high CP content (up to 23.47%) and/or low NDF and ADF contents. The highest CP content in red clover was recorded in population CD-18 (21.89%), while the lowest NDF and ADF contents were determined in populations CD-19 and CD-4, respectively. High RFV was determined in alfalfa populations L-10, 12, 20, 15, 16, 8, 11, and 17 (prime fodder), and in red clover populations CD-4, 8, 16, 14, and 19 (premium-quality fodder). The identified superior alfalfa and red clover populations will be used to improve the nutritional value of forage crops in our breeding program, which will lead to the release of novel cultivars with improved forage quality.